Pengambilan Hukum Dari Hadis-Hadis Mukhtalif Menurut Ulama Hadis Dan Ulama Fikih - Fathul Mu’in; Ananda Prayogi; Babun Najib (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
Contradictory hadiths or mukhtalif hadiths often confuse the people in determining a law. Therefore, this research is about how fiqh scholars and hadith scholars adopt laws that originate from these contradictory hadiths. The object of this research is the method used by fiqh and hadith scholars as a basis for making laws and comparing them so that the formula or formula can be known. This research is a literature study using content analysis as a data analysis technique. The results of this study indicate that the hadith scholars and fiqh scholars have the same order of methods in resolving contradictory hadiths, namely the al-jam'u, nasakh, tarjih and tawaqquf methods. However, Imam Abu Hanifah has a different order, namely the nasakh, tarjih, al-jam'u and tawaqquf methods. In comparison to the methods used by the two scholars, both the muhaddisin and the fuqaha' agree to prioritize the al-jam'u method as an effort not to confuse one hadith with another. However, it is different from Imam Abu Hanifah who prioritizes the nasakh method over the al-jam'u method so that as a consequence there are hadiths that are not used.